2008
DOI: 10.1143/jjap.47.5955
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Readout of 75 Gbyte Disc Made with Conventional Optical Disc Manufacturing Equipment

Abstract: We study precision electroweak constraints within a RS1 model with gauge fields and fermions in the bulk. The electroweak gauge symmetry is enhanced to SU(2) L × SU(2) R × U(1) B−L , thereby providing a custodial isospin symmetry sufficient to suppress excessive contributions to the T parameter. We then construct complete models, complying with all electroweak constraints, for solving the hierarchy problem, without supersymmetry or large hierarchies in the fundamental couplings. Using the AdS/CFT correspondenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…We had reported the evaluation of a 100 GB disc without a cover film with the SIL-equipped tester in ISOM2009. 7,8) In this study, we used the SIL tester with a modified pick up. The PUH was optimized to the disc with a cover film.…”
Section: Playback Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We had reported the evaluation of a 100 GB disc without a cover film with the SIL-equipped tester in ISOM2009. 7,8) In this study, we used the SIL tester with a modified pick up. The PUH was optimized to the disc with a cover film.…”
Section: Playback Resultsmentioning
confidence: 99%
“…3.2 Master structure and material Some materials were proposed for the thermal recording media. [4][5][6] We chose a dielectric material (ZnS-SiO 2 ) [7][8][9] as the recording material, because this material has two characteristics for the recording material in the mastering process. One is the effect of heating, and the other is the crystal structure after recording.…”
Section: Process Flowmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It can exhibit a large capacity and a highdata transfer rate towards recording next-generation ultrahigh-definition television [i.e., Super Hi-Vision (SHV), 7320 Â 4320 pixels] video signals 17,18) for home-use. Fourfold higher density recording using NFR optical disks with 1.2-mm-thick disks has been reported, 12,14) and studies of larger capacity using multilayer recording using NFR have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These days, many impressive results of technical candidates for the next-generation optical discs have been reported in this field. The technical candidates include volumetric storage technology, [1][2][3][4][5][6] near-field technology, [7][8][9][10][11][12][13] and multilayer technology, [14][15][16][17][18][19][20] which is a volumetric storage technology. Among them, multilayer technology has a lot of advantages such as storage capacity, backward compatibility, and system practicability, and so on.…”
Section: Introductionmentioning
confidence: 99%